PENGARUH SISTEM INFORMASI, KOMITMEN MANAJEMEN, BUDAYA ORGANISASI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Nurviasari, Rizki; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test empirically the influence of information system, management commitment and organization culture to the institution performance accountability of Local Government of Surabaya. The population is the head of department and the head of the section in the local apparatus work unit (SKPD) in the environment of Local Government of Surabaya. The sample collection technique has been done by using purposive sampling method. The data collection has been done by using survey method which has been obtained by issuing questionnaires to the respondents. The data has been obtained from the deployment of 90 questionnaries to employees maker and compilers of the report on accountability and performance of government (LAKIP) in the local apparatus work unit of surabaya. A total of 86 questionnaries were retured and 80 questionnaires (89%) filled out completely and can be processed. The analysis technique has been done by performing multiple linear regressions analysis model. The result of the research shows that information system has positive influence to the institution performance accountability of Local Government of Surabaya, management commitment has positive influence to the institution performance accountability of Local Government of Surabaya and the organization culture has positive influence to the institution performance accountability of Local Government of Surabaya.Keywords: Information System, Management Commitment, Organization Culture, Performance Accountability.